PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL PICTURE AND PICTURE DI SEKOLAH DASAR - Antoni, Juli; Sugiyono, Sugiyono; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research method used is descriptive with the form of classroom action research, and is collaborative. Data collection techniques used are direct observation and questionnaires. The data analysis technique used is using the average calculation formula. The subject of this research is the students of VA class of Primary School 16 Pontianak City totaling 27 students. This research was conducted in 3 cycles with the result 1) the average ability of the teacher to plan the learning, that is as follows in cycle I 3.14, in cycle II 3,27, at cycle III 3,61. 2) the average ability of teachers to implement the learning that is as follows in cycle I 3.01, in cycle II 3.20, in cycle III 3.64. 3) the average of student learning outcomes are as follows, in the first cycle 55,92, in cycle II 74,81, and at cycle III 86,29. From the data obtained can be concluded picture and picture model can improve student learning outcomes.Keywords: Upgrade, Learn Outcome, Pictures and Pictures Model.